The reliability and validity of the pupil behaviour questionnaire: a child classroom behaviour assessment tool. Issue 4 (2nd October 2018) - Allwood, Matt; Allen, Kate; Price, Anna; Hayes, Rachel; Edwards, Vanessa; Ball, Susan; Ukoumunne, Obioha C; Ford, Tamsin
ABSTRACT: This paper assesses the reliability and validity of the teacher-completed Pupil Behaviour Questionnaire (PBQ), by comparing it to the already extensively validated teacher-completed Strengths and Difficulties Questionnaire (SDQ). Participants included 2074 primary school children participating in a universal school-based trial and 41 vulnerable children who were taking part in a study exploring the impact of exclusion from school. Exploratory factor analysis results (first factor accounts for 80.8% of the variation in the items) and the high Cronbach's alpha value of 0.85 indicate that the PBQ consists of one substantive factor/dimension. Strong correlations between the total PBQ score and the conduct sub-scale (Spearman's correlation coefficient (rs ) = 0.67) and total difficulties score (rs = 0.59) of the SDQ indicate convergent validity. This study suggests that the PBQ is a reliable measure, and provides some evidence of validity. Further work is needed to test the PBQ in an older, more diverse populations and to measure sensitivity to change.